Dengue diagnosis in an endemic area of Peru: Clinical characteristics and positive frequencies by RT-PCR and serology for NS1, IgM, and IgG - Palomares-Reyes C. (2019)
Huánuco is a central eastern region of Peru whose geography includes high forest and low jungle, as well as a mountain range that constitutes the inter-Andean valleys. It is considered a region endemic for dengue due to the many favorable conditions that facilitate transmission of the virus.